2009
DOI: 10.3892/or_00000350
|View full text |Cite
|
Sign up to set email alerts
|

Primary non-Hodgkin's lymphoma of the spine with neurologic compression treated by radiotherapy and chemotherapy alone or combined with surgical decompression

Abstract: Abstract. Neurologic compression is a disastrous consequence for the patients with primary non-Hodgkin's lymphoma (NHL) of the spine, and such a condition has not been carefully taken into account in the treatment guidelines. The aim of this study was to compare the effect of radiotherapy and chemotherapy alone or combined with surgical decompression on primary NHL of the spine with neurologic compression. Sixteen patients with primary NHL in the vertebrae of the spine were treated between 1994 and 2006. Thirt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
1
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 17 publications
1
30
1
2
Order By: Relevance
“…Our results suggest that surgical decompression may result in superior overall survival of DLBCL patients with spinal compression, even though statistical significance was lacking. This result is in contrast to the findings of a study conducted by Peng and colleagues that showed the 5-year overall survival rates for patients with primary non-Hodgkin's lymphoma of the spine with neurological compression in surgical and nonsurgical groups were 60% and 100%, respectively [6]. More well-designed clinical trials will therefore be required to clarify this controversial conclusion.…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…Our results suggest that surgical decompression may result in superior overall survival of DLBCL patients with spinal compression, even though statistical significance was lacking. This result is in contrast to the findings of a study conducted by Peng and colleagues that showed the 5-year overall survival rates for patients with primary non-Hodgkin's lymphoma of the spine with neurological compression in surgical and nonsurgical groups were 60% and 100%, respectively [6]. More well-designed clinical trials will therefore be required to clarify this controversial conclusion.…”
Section: Discussioncontrasting
confidence: 70%
“…As DLBCL usually responds to chemotherapy within days, chemotherapy may be able to replace decompression surgery in DLBCL patients who have MASC. However, a study conducted by Peng and colleagues showed a negative impact of decompression surgery on survival in patients with primary spinal lymphoma complicated by spinal cord compression [6]. Owing to a lack of statistical power in that study, it remains unclear whether surgical decompression can benefit DLBCL patients with MASC.…”
Section: Introductionmentioning
confidence: 99%
“…Primary lymphoma of bone usually responds well to a combination of radio- and chemotherapy regimens, and an overall response rate of 94% and a 5-year survival rate better than that achieved by most other primary osseous malignancies have been reported2). Peng et al10) also reported that combined chemotherapy and radiotherapy is the ideal treatment for primary non-Hodgkin's lymphoma of the spine, where as the survival is not influenced by the surgical or non-surgical treatment. In cases of severe pain or neurological deficits, however, early surgical decompression and stabilization is mandatory13).…”
Section: Discussionmentioning
confidence: 99%
“…For Peng et al [10] the ideal treatment of vertebral lymphoma is chemotherapy combined with radiotherapy. Park et al [9] however argue that treatment of spinal lymphoma must be multifactorial including surgery, radiotherapy and chemotherapy.…”
Section: Discussionmentioning
confidence: 99%